Mapping the Path from High-Performance Work Systems to Employee Resilience: A Systematic Review - Qizi, Karimova Aziza Lazizjon; Ciptagustia, Annisa; Askolani, Askolani (Eastasouth Institute, 2025)
This systematic review investigates the relationship between High-Performance Work Systems (HPWS) and employee resilience. As organizations face increasing volatility and uncertainty, understanding how HR practices contribute to workforce resilience has become essential. A systematic search was conducted across Scopus, Web of Science, and Google Scholar for peer-reviewed articles published between 2012 and 2024. Following PRISMA guidelines, 47 relevant studies were selected based on inclusion criteria focusing on empirical or conceptual linkages between HPWS components (e.g., training, empowerment, performance appraisal) and employee resilience outcomes. The review identifies three central themes: (1) HPWS fosters resilience through skill-building and autonomy-enhancing practices; (2) psychological safety, leadership support, and organizational culture act as key mediators or moderators; (3) resilient employees contribute to adaptability, engagement, and organizational sustainability. The review also reveals a geographic and methodological gap—most studies are concentrated in developed economies and rely on cross-sectional data. This article offers a synthesized pathway between HPWS and employee resilience, integrating multiple theoretical lenses including the AMO framework and Conservation of Resources Theory. It also provides HR practitioners with practical guidance on designing resilience-enhancing systems. HPWS, when strategically implemented, can significantly enhance employee resilience. Future research should explore longitudinal impacts and cultural contexts to deepen understanding